Gridded EM300 multibeam-echosounder bathymetry of cruise 64PE284 - Paul Wintersteller (PANGAEA, 2018)
Bathymetry based on multibeam echosounder (MBES) data recorded during RV PELAGIA cruise 64PE284 between 18.02.2008 and 09.03.2008 at the Moroccan continental margins. The main objective of this cruise was the investigation of cold-water coral ecosystems in the Gulf of Cádiz. The study of these partly quite small-scale systems requires besides standard sampling methods also innovative technology, therefore the ROV CHEROKEE was used for observations. Description of the data source: During the RV PELAGIA cruise 64PE284 the Kongsberg EM300 multibeam echosounder with a nominal sounding frequency of 30 kHz was utilized. 135 beams are formed for each ping with with a 1°(Tx)/2°(Rx) footprint while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult https://www.whoi.edu/cms/files/instruments/2006/9/160765ad_EM300_Product_specific_lr_13565.pdf. The EM300 was recording constantly within the permitted areas designated to bathymetry surveys. The EM300 system performed as expected during the cruise. Responsible person during this cruise / PI: Ruud Groenewegen (ruud.Groenewegen@nioz.nl). Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System suite (Caress, D.W., and D.N. Chayes, MB-System Version 5.5, open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. CTD measurements during the 64PE284 cruise were sufficient to represent the changes in the sound velocity throughout the study area. Further roll, pitch and heave or leverarms corrections were not necessary for the 64PE284 data. Bathymetric data has been manually cleaned for existing artefacts with mbeditviz. NetCDF (GMT) grids of the product and the statistics were created using mbgrid. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. The currently published bathymetric grid of the cruise has a resolution of 125 m. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: D. Hebbeln (dhebbeln@marum.de) CR: https://elib.suub.uni-bremen.de/ip/docs/00010373.pdf CSR: not yet available